Hb Adana (HBA2 or HBA1: c.179G > A) and alpha thalassemia: Genotype–phenotype correlation. Issue 9 (11th May 2018) - Singh, Sharon A.; Sarangi, Susmita; Appiah‐Kubi, Abena; Hsu, Peihong; Smith, W. Byron; Gallagher, Patrick G.; Glader, Bertil; Chui, David H. K.
Abstract: Alpha thalassemia due to nondeletional mutations usually leads to more severe disease than that caused by deletional mutations. Devastating outcomes such as hydrops fetalis can occur with two nondeletional mutations, therefore warranting DNA‐based workup for suspected carriers with subtle hematological abnormalities for family counseling purposes. We describe three cases with hemoglobin (Hb) Adana, a nondeletional alpha chain mutation, compounded with an alpha globin gene deletion resulting in thalassemia intermedia. We review the literature, draw genotype–phenotype correlations from published cases of Hb Adana, and propose that this correlation can be used by clinicians to help direct diagnostic studies and urge hematologists to thoroughly workup high‐risk patients.